The Influence of Health Counseling About Danger Signs for Infants Aged 0-12 Months on the Activeness of Mothers Going to Posyandu at Posyandu Balla Satanetean, Balla District, Mamasa Regency - Dewi Sartika; Masluroh Masluroh (CV. Inara, 2024)
Background Based on the World Health Organization (World Health Organization) IMR in an outline which is the Infant Mortality Rate of 19 per 1000 KH. This value is still quite far from the target of the SDGs (Sustainable Development Goals) which set in 2030 the IMR of 12 per 1000 live births (World Health Organization, 2016). The results of the 2017 Indonesian Demographic Health Survey (IDHS) provide encouraging information related to the infant and child mortality rates. priohutomo at the launching event and colloquium on the results of the 2017 SDKI in Jakarta, Tuesday (9 or 10 or 2018). Objective: To determine the effect of health education about danger signs for babies aged 0-12 months on the activity of posyandu mothers at Posyandu Balla Satanetean, Balla District, Mamasa district. Research results: From the results of the research and conducting counseling and distributing questionnaires to 37 respondents so that more mothers did not take part in counseling immediately after giving birth because it was caused by the mother's lack of insight regarding the characteristics of threats to babies so that it caused failure to attend counseling. failed counseling will affect the health of babies in mothers who have babies because it is known that the more active the mother is in participating in counseling and being active in the posyandu will improve the health of the baby both. Conclusions and suggestions: Education also affects mothers who are less active at posyandu, mothers who have high educational status will be more active in participating in health education for their babies and more active at posyandu.